Novel Machado-Joseph disease-modifying genes and pathways identified by whole-exome sequencing - Raposo, Mafalda (2021)
Funding Information: This work was funded by FEDER - Fundo Europeu de Desenvolvimento Regional funds through the COMPETE 2020 - Operacional Programme for Competitiveness and Internationalisation (POCI), Portugal 2020 , and by Portuguese funds through FCT - Fundação para a Ciência e a Tecnologia / Ministério da Ciência, Tecnologia e Ensino Superior in the framework of the project PTDC/DTP-PIC/2638/2017 ( POCI-01-0145-FEDER-016592 ); GenomePT ( POCI-01-0145-FEDER-022184 ); ICVS Scientific Microscopy Platform , member of the national infrastructure PPBI - Portuguese Platform of Bioimaging ( PPBI-POCI-01-0145-FEDER-022122 ; by National funds , through the Foundation for Science and Technology (FCT) - project UIDB/50026/2020 and UIDP/50026/2020 ; and by the project NORTE-01-0145-FEDER-000013 , supported by Norte Portugal Regional Operational Programme (NORTE 2020), under the PORTUGAL 2020 Partnership Agreement, through the European Regional Development Fund (ERDF) . MR is supported by FCT ( CEECIND/03018/2018 ). ARVM ( SFRH/BD/129547/2017 ) and AFF ( SFRH/BD/121101/2016 ) are supported by a PhD grant financed by FCT . CB is supported by the Multiple System Atrophy Trust and Alzheimer's Research UK . MDC received funding from National Ataxia Foundation (NAF) and from FCT ( SFRH/BPD/101925/2014 ); DV-C received a grant from FCT ( SFRH/BD/147826/2019 ). Publisher Copyright: © 2021